Sistem Update Firmware Perangkat IoT Menggunakan Teknik OTA Berbasis HTTP - Krisna Madani; Rahmi Hidayati; Uray Ristian (JURIKOM (Jurnal Riset Komputer), 2022)
Firmware is software that resembles an operating system and embedded in the hardware. On Internet of Things (IoT) devices, the already installed firmware will not be updated for the specified time or will not even be updated at all. This is because the firmware is considered a system whose needs and functions do not need to be changed. However, in reality the firmware that is already installed and is being run definitely needs a change. The update process generally also uses conventional methods, namely by connecting devices on a computer using a cable. This method is of course not effective and efficient to do, especially if you have many devices installed and running. Therefore, in this study, an update system was created to update devices using the internet network. The update system built on this study using Over The Air (OTA) techniques and Hypertext Transfer Protocol (HTTP). In testing the update process with 3 IoT devices simultaneously, the average time needed by device 1, device 2 and device 3 is 43 seconds, 44 seconds and 45 seconds. In the QoS analysis carried out, the results obtained throughput of 100% (very good), packet loss of 0% (very good), average delay of 93,931ms (very good) and jitter of 98,948ms (medium) on the network used for updating